Upper airway stimulation for obstructive sleep apnea: results from the ADHERE registry - Boon, Maurits; Huntley, Colin; Steffen, Armin; Maurer, Joachim T.; Sommer, Ulrich; Schwab, Richard; Thaler, Erica; Soose, Ryan; Chou, Courtney; Strollo, Patrick; Kezirian, Eric J.; Chia, Stanley; et al. (Otolaryngology - head and neck surgery, 2018)
Objective: Upper airway stimulation (UAS) is an alternative treatment option for patients unable to tolerate continuous positive airway pressure (CPAP) for the treatment of obstructive sleep apnea (OSA). Studies support the safety and efficacy of this therapy. The aim of this registry is to collect retrospective and prospective objective and subjective outcome measures across multiple institutions in the United States and Germany. To date, it represents the largest cohort of patients studied with this therapy. Study design: Retrospective and prospective registry study. Setting: Ten tertiary care hospitals in the United States and Germany. Subjects and methods: Patients were included who had moderate to severe OSA, were intolerant to CPAP, and were undergoing UAS implantation. Baseline demographic and sleep study data were collected. Objective and subjective treatment outcomes, adverse events, and patient and physician satisfaction were reviewed. Results: The registry enrolled 301 patients between October 2016 and September 2017. Mean ± SD AHI decreased from 35.6 ± 15.3 to 10.2 ± 12.9 events per hour (P < .0001), and Epworth Sleepiness Scale scores decreased from 11.9 ± 5.5 to 7.5 ± 4.7 (P < .0001) from baseline to the posttitration visit. Patients utilized therapy for 6.5 hours per night. There were low rates of procedure- and device-related complications. Clinical global impression scores demonstrated that the majority of physicians (94%) saw improvement in their patients’ symptoms with therapy. The majority of patients (90%) were more satisfied with UAS than CPAP. Conclusions: Across a multi-institutional registry, UAS therapy demonstrates significant improvement in subjective and objective OSA outcomes, good therapy adherence, and high patient satisfaction.
Gesehen am 02.04.2020